Malnutrition risk as a predictor of quality of life and skeletal muscle depletion following upper gastrointestinal cancer diagnosis: A longitudinal analysis - Lauren Hanna; Kay Nguo; Judi Porter; Daniel Croagh; Catherine E Huggins (The Journal of Nutrition, Health and Aging, 2025)
Objectives: Low skeletal muscle index (SMI) and radiodensity (SMD) are established prognostic indicators in cancer. This study investigated risk factors for low and decreasing SMI and low SMD in upper gastrointestinal cancer and examined the influence of malnutrition risk on the association between SMI and health-related quality of life (HRQOL). Design: Longitudinal analysis of randomised controlled trial outcome data. Setting: Three health services in Victoria, Australia. Participants: Adults newly diagnosed with oesophageal, gastric or pancreatic cancer. Measurements: Outcomes assessed at diagnosis, and three- and six-month follow-up. SMI and SMD were assessed via computed tomography imaging analysis, with low values determined using established sex-specific thresholds. Malnutrition risk was assessed using the Patient Generated Subjective Global Assessment (Short Form), and HRQOL with the EORTC QLQ-C30. Multiple logistic regression identified risk factors for low SMI and low SMD at baseline, and SMI decline (≥5%) from baseline to 3 months. Associations between SMI and HRQOL were examined using multiple linear regression, adjusting for malnutrition risk. Results: Among 105 participants (43% oesophageal, 20% gastric, 37% pancreatic cancer), older age predicted low SMI and low SMD. Low SMI risk was higher in females and lower with higher BMI. At three months, 57% (37/65) experienced ≥5% SMI loss, associated with higher malnutrition risk, higher baseline SMI, and post-diagnosis weight loss. Malnutrition risk was a strong independent predictor of poorer HRQOL score at all timepoints. Lower or decreasing SMI (≥5%) was also independently associated with poorer HRQOL on some scales. Conclusion: Malnutrition risk independently predicted lower HRQOL and muscle loss, and may confound the relationship between SMI and HRQOL. As a modifiable factor, addressing malnutrition risk could improve HROQL and preserve muscle in upper gastrointestinal cancer. Trial registration: Australian New Zealand Clinical Trials Registry, 27 January 2017 (12617000152325).